Expression of beta-catenins and cadherins by follicular dendritic cells in human lymph nodes - Müller, J; Tvrdík, D; Dvorák, R; Djaborkhel, R; Mandys, V; Bednár, B; Raska, I; Lojda, Z (Acta histochemica, 2000)
In lymph nodes, dendritic cells form a complex meshwork and are linked by intercellular junctions. Intercellular junctions contribute to the integrity of lymphatic follicles and can potentially be affected by malignant processes in neighbouring B cells. We examined whether transmembrane molecules that constitute "adherens junctions" are present in follicular dendritic cells of normal human lymph nodes. We found that follicular dendritic cells but not interdigitating dendritic cells or sinus lining cells expressed cadherin molecules. Follicular dendritic cells also expressed beta-catenin but not vinculin. The cadherin molecules, which were identified in situ with the use of a monoclonal pan-cadherin antibody, were not recognized by antibodies to E-cadherin, N-cadherin or P-cadherin. Intrafollicularly, cadherins were clearly colocalized with beta-catenins, in a dot-like fashion. We also detected intrafollicular expression of desmogleins and desmosomal plaque proteins. These findings indicate the presence of desmosomes within the dendritic meshwork. However, pan-cadherin reactivity was not only colocalized with desmoglein immunoreactivity that was abundantly present. Immunoprecipitation showed that pan-cadherin reactivity was absent in fractions of desmosomal plaque proteins or pan-desmogleins. We speculate that complexes of cadherins of an unknown subclass and beta-catenins form non-desmosomal intercellular junctions in the intrafollicular dendritic meshwork.
Keywords: Microscopy, Fluorescence; imunoblotting; Humans; beta-katenin; dendritické buňky; Precipitin Tests; Cadherins; fluorescenční mikroskopie; Phenotype; Dendritic Cells, Follicular; lidé; Immunohistochemistry; imunohistochemie; Trans-Activators; Cytoskeletal Proteins; Lymph Nodes; cytoskeletální proteiny; lymfatické uzliny; trans-aktivátory; Dendritic Cells; fenotyp; folikulární dendritické buňky; precipitinové testy; kadheriny; Receptors, Complement 3b; beta Catenin; Immunoblotting; receptory komplementu 3b